2020
DOI: 10.1371/journal.pone.0227138
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of diagnostic algorithms including lateral-flow urine lipoarabinomannan for HIV-positive patients with symptoms of tuberculosis

Abstract: BackgroundTuberculosis (TB) is the leading cause of death among HIV-positive patients. We assessed the cost-effectiveness of including lateral-flow urine lipoarabinomannan (LF-LAM) in TB diagnostic algorithms for severely ill or immunosuppressed HIV-positive patients with symptoms of TB in Kenya. MethodsFrom a decision-analysis tree, ten diagnostic algorithms were elaborated and compared. All algorithms included clinical exam. The costs of each algorithm were calculated using a 'micro-costing' method. The effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Based on cohorts recruited in South Africa and other African countries, modelling studies have estimated that implementation of AlereLAM within TB diagnostic algorithms is also cost-effective. 14,15 Simplifying the criteria for AlereLAM as far as possible would likely improve its uptake and implementation, but this needs to be balanced against diagnostic yield of the criteria considered, which in turn impacts cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on cohorts recruited in South Africa and other African countries, modelling studies have estimated that implementation of AlereLAM within TB diagnostic algorithms is also cost-effective. 14,15 Simplifying the criteria for AlereLAM as far as possible would likely improve its uptake and implementation, but this needs to be balanced against diagnostic yield of the criteria considered, which in turn impacts cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Based on cohorts recruited in South Africa and other African countries, modelling studies have estimated that implementation of AlereLAM within TB diagnostic algorithms is also cost-effective. 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…The prior health economics analyses of the rapid TB testing in high-burden countries were mostly focused on the Xpert and AlereLAM. Three decision-analytic models and a microsimulation model analysis showed that the addition of AlereLAM to Xpert detected more TB cases and was cost-effective (ICER range: 24 USD/DALY-731 USD/DALY averted; 420-810 USD per years-of-life saved (YLS)) for HIV-positive patients in high-burden settings of Malawi, Uganda, South Africa, and Kenya [53][54][55][56]. A recent cost-effectiveness analysis by evaluated Xpert, Xpert with AlereLAM and Xpert with FujiLAM, and reported that ICER of Xpert+ Fuji-LAM versus Xpert alone was 830 USD/YLS in South Africa and 440 USD /YLS in Malawi [36].…”
Section: Plos Onementioning
confidence: 99%
“…Eight countries Accounted for 87% of the world's total new TB cases in 2018 with India leading the tally, followed by China, Indonesia, the Philippines, Pakistan, Nigeria, Bangladesh, and South Africa. Treatment adherence is a major factor in the failure of the pulmonary TB treatment program &Yakhelef et al, 2020.…”
Section: Introductionmentioning
confidence: 99%